Bibliometric Analysis: The Application of Augmented Reality in the Field of Education in the World - Triani, Deswinta; Sudarshana, Midigama Liyanage (Indonesian Journal of Pedagogy and Teacher Education, 2025)
The research conducted is a bibliometric analysis related to the application of augmented reality in the field of education in the world. It aims to investigate its application in world education, how it affects students' learning skills, and provides insights for future educational practices. Utilizing the Publish or Perish tool, the research methodology employed a keyword search for "Augmented Reality" and derived from Scopus from 2018 to 2024. A specific topic of "in Education" was then chosen, yielding 52 relevant papers out of the initial 133 search articles. The Mendeley and Vosviewer apps are used to gather metadata to generate visualizations (Network and Density) of the databases containing the first and last search results. According to the research findings that have been visualized, augmented reality is required in the field of education to support the learning process itself and enhance the abilities and learning outcomes of high school students. According to earlier studies, augmented reality has a significant positive impact on both teachers and pupils when used in secondary education.